2015
DOI: 10.18632/oncotarget.4160
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer cell metabolism in pancreatic adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is expected to become the second leading cause of cancer death by 2030. Current therapeutic options are limited, warranting an urgent need to explore innovative treatment strategies. Due to specific microenvironment constraints including an extensive desmoplastic stroma reaction, PDAC faces major metabolic challenges, principally hypoxia and nutrient deprivation. Their connection with oncogenic alterations such as KRAS mutations has brought metabolic reprogramming to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 168 publications
(152 reference statements)
1
95
0
4
Order By: Relevance
“…Indeed, in PDA, a well-reported heterogeneous tumor (38), hypoxia (39), inflammatory response (40), and extracellular matrix (8) are predominant factors that could modulate such dialogue. At present, most PDA patients are following one of the baseline therapies made of gemcitabine, FOLFIRINOX, or gemcitabine plus nab-paclitaxel (except for patients enrolled in phase 2/3 protocols).…”
Section: Anxa6 Lrp1 and Tsp1 Expression In Pda Is Mainly Driven By mentioning
confidence: 99%
“…Indeed, in PDA, a well-reported heterogeneous tumor (38), hypoxia (39), inflammatory response (40), and extracellular matrix (8) are predominant factors that could modulate such dialogue. At present, most PDA patients are following one of the baseline therapies made of gemcitabine, FOLFIRINOX, or gemcitabine plus nab-paclitaxel (except for patients enrolled in phase 2/3 protocols).…”
Section: Anxa6 Lrp1 and Tsp1 Expression In Pda Is Mainly Driven By mentioning
confidence: 99%
“…NEUZILLET et al, PDAC state of the art 13 for tumor initiation and progression (Hanahan & Weinberg, 2011). Both oncogenes, with a driver role for oncogenic KRAS, and the tumor microenvironment are involved in this process (Cairns, Harris, & Mak, 2011;Cohen et al, 2015). The extensive and poorly vascularized desmoplastic stromal reactions in PDAC leads to tumor hypoxia and nutrient deprivation, yet without evidence of major cell death (Bergers & Hanahan, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This suggests that pancreatic cancer cells adapt to metabolically challenging survival conditions in their microenvironment early in tumor development. Several changes occur in response to oxygen and nutrient deprivation: increased glycolysis even in aerobic conditions, as well as increased amino acid (AA) uptake derived from protein degradation, protein glycosylation, and fatty acid synthesis (Cohen et al, 2015;Ryan, Hong, & Bardeesy, 2014b). In addition, recycling and scavenging of cellular and extra-cellular components through autophagy and macropinocytosis have been shown to be applicable in PDAC (Cohen et al, 2015;Ryan et al, 2014b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover; it is known that cancer cells compared to normal cells have specific metabolic dependencies, they have increased need of the amino acid glutamine (41). Kras is responsible for reprogramming glutamine metabolism in PDAC (42). Targeting the Warburg effect has shown that the p53 status of PDAC determined the response to inhibitors of the enzyme lactate dehydrogenase-A (43).…”
Section: Cell Metabolism In Pancreatic Cancermentioning
confidence: 99%